Incidence and characteristics of patients with congenital defects at the Pereira Rossell Hospital’s Neonatology Department in 2016-2020: 5 years experience (Archives of Pediatrics of Uruguay, 2022)
Congenital birth defects are morphological disturbances originated during gestation and present in up to 5% of live births. They have multiple etiologies, in 90% of cases of multifactorial origin. A longitudinal, prospective, observational study was carried out and it included all patients with congenital birth defects in 2016-2020. The main objective of this study was to determine the incidence of newborns with congenital birth defects between 2016 and 2020, to determine their distribution by organ, to describe their demographic characteristics, to calculate the prevalence of prenatal diagnosis and to identify maternal risk factors. We obtained an incidence of 1,7% (423 affected newborns in 24870 live births), 34,98% had prenatal diagnoses. The cardiovascular system was the most frequently affected and when classified by individual birth defect, the most frequently observed was gastroschisis with 15.28 cases in 10,000 live births. Gestational diabetes was the maternal risk factor most frequently observed with 17, 25%. This study enabled us to know the incidence of congenital birth defects and their distribution by different organs at our center. These surveillance systems are key to identify areas of potential improvement that might enable us to mitigate morbidity and mortality in this group of patients
Keywords: Congenital abnormalities; Congenital heart defects; Newborn; Prenatal diagnosis